PENERAPAPAN METODE K-MEANS CLUSTERING DALAM PENGELOLAAN KESEJAHTERAAN SOSIAL DI DESA PENTUR - Hakim, Rifaldi Ali; Harjanto, Sri; Wibowo, Ari (STMIK Sinar Nusantara, 2024)
Managing aid to improve social welfare in the Pentur village environment is carried out conventionally and requires special attention so that it is not misdirected. Community welfare can be seen from several aspects, namely sufficient income, adequate education and health. The application of the k-means clustering method in managing social welfare in Pentur village will facilitate the performance of the village government in improving the social welfare of its citizens. The clustering process, with the calculations used are variables based on family dependents, monthly income of the head of the family and property ownership. K-Means clustering is a method that divides data into groups that have objects with the same characteristics. The results of applying k-means clustering for the Social Welfare cluster are divided into 3 parts, namely cluster 1 or low gets a result of 11, cluster 2 or medium gets a result of 11, and cluster 3 or high gets a result of 3. The results of the validity test are carried out using calculations silhouette coefficient and produces a global s(i) value of 0.360222796 and can be said to be good because there are no numbers that show < 0 or no over lapping occurs so it can be said that the data that has been processed has good quality.